Korelasi Antara Kawasan Situs Nol Kilometer Dengan Pembentukan Identitas Kota Yogyakarta - Santika, Denny (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Zero Kilometer Area is a new image of Yogyakarta, the transformation of the value of heritage, initiated by the municipal government of Yogyakarta with the relevant institutions therein, Non Government Organisations, and the humanists. Their Regions initiated with the aim to upgrade the trading value of tourism and also to strengthen the identity of Yogyakarta people. The purpose of this research is to answer whether the placement of Zero Kilometer Area in the current location is already appropriate, viewed from historical and archaeological aspects and can be considered as the center of Yogyakarta City. This is the key to create Yogyakarta city’s image in accordance with the original culture and identity. The data is gathered by the field observations, interviews, and literature study, and also the research is described by descriptive analytical way. The essence idea of this research is to straighten the placement of Zero Kilometer area, which is traced by archaeological and historical approach.